Regulation and Taxation of Casinos under State-Monopoly, Private Monopoly and Casino Association Regimes - Hasret Benar; Glenn Jenkins (Queen's University, Department of Economics, 2006)
This paper considers alternative forms of regulation and taxation of the casino sector. The model considers the situation of a typical tourist destination country that is using casinos to attract and entertain foreign tourists. The objective is to invest in the sector efficiently while maximizing the amount of government revenue or profits accruing to the country. The regulator must determine how the price of gambling will be set, how many casinos will be allowed to enter the industry and the form and rates of taxation. Four alternative forms of regulation are considered: price regulation, state-owned monopoly, private monopoly and casino association regulation. Turnover taxes on the amount of funds gambled and also annual taxation of the fixed costs of the casinos are evaluated. Applications of the models are carried out for North Cyprus. The conclusion is that the economic efficiency costs and the revenue losses from the absence of effective regulation in these tourist destinations can be very substantial with welfare costs equal to the approximately 75 percent of the tax revenue generated by this sector. Furthermore it shows that while a tax on turnover can be efficient in the case of a competitive industry or a cartel association form of regulation, it will be distortionary if a multi-plant private monopoly is controlling the sector. In contrast a tax on fixed costs will lead to an efficient result in the case of a competitive industry, but it will lead to economic inefficiencies if the sector is regulated by a casino association that controls the number of casino entering the sector.
Keywords: H21; H32; 330; Casino regulation; taxation; state-monopoly; welfare cost